2022
DOI: 10.3390/children9030445
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Advance Care Planning: What Matters Most for Parents of Children with Rare Diseases

Abstract: Few studies have described the goals and wishes of parents caring for their children with rare diseases, specifically when children are unable to communicate their preferences directly. The purpose of this study was to describe the parent’s understanding of their child’s illness, goals of care, and what mattered most to their child from the parent’s perspective. Six families completed a feasibility study of the FAmily CEntered (FACE)-Rare pACP intervention. Qualitative content analysis was performed on transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Third, across months and years of received palliative care, maintaining the child’s health continued to be important to parents. The few studies that have examined parents’ goals at different times have been retrospective or 1-time cross-sectional studies with qualitative data (eg, in 1 study visit, parents were asked to recall and report on goals at multiple time points in the past) . Lastly, we found that parents who differentiated the GOCs by importance scores had more stable goal priorities over time, an issue which, to out knowledge, has not been examined before.…”
Section: Discussionmentioning
confidence: 58%
“…Third, across months and years of received palliative care, maintaining the child’s health continued to be important to parents. The few studies that have examined parents’ goals at different times have been retrospective or 1-time cross-sectional studies with qualitative data (eg, in 1 study visit, parents were asked to recall and report on goals at multiple time points in the past) . Lastly, we found that parents who differentiated the GOCs by importance scores had more stable goal priorities over time, an issue which, to out knowledge, has not been examined before.…”
Section: Discussionmentioning
confidence: 58%
“…Giving authority to the family means opening the way for the family to know the strength, ability of the family in caring for children. (Fratantoni et al, 2022)…”
Section: Resultsmentioning
confidence: 99%
“…Giving authority to the family means opening the way for the family to know the strength, ability of the family in caring for children. (Fratantoni et al, 2022) Philosophically, the involvement of parents and children in their own care is very important. This does not mean simply asking them what they think or talk about with parents and not for children (of course, this is age related).…”
Section: Epistemological Study Of Family Centered Care In Children Wi...mentioning
confidence: 99%
“…The question of whether or not pediatric advance care planning (pACP) matters to the parents of children with rare diseases, particularly for those children who are unable to participate in decision making, is only beginning to be explored. Fratantoni and colleagues beta tested a pACP intervention with six families [ 10 ]. Their article describes a qualitative analysis of structured interviews examining what parents thought mattered most to their child and what they would want their doctor to know.…”
Section: Contributions To the Special Issuementioning
confidence: 99%